The role of the community pharmacist in veterinary patient care: a cross-sectional study of pharmacist and veterinarian viewpoints - Mary E. Fredrickson; Hayley Terlizzi; Rikki L. Horne; Stanley Dannemiller (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: The role of the community pharmacist is rapidly expanding to encompass the care of veterinary patients in the United States of America This change makes it imperative for pharmacists and veterinarians who practice in community settings to establish mutual agreement on the roles of pharmacists in the care of these patients. Objective: To examine community-based pharmacist and veterinarian viewpoints on interprofessional collaboration and the role of the community pharmacist in veterinary patient care. Methods: Cross-sectional surveys were sent to pharmacists and veterinarians who practice in a community setting in Ohio. Surveys collected demographic information and addressed the following themes: attitudes toward collaboration, perceived roles of the pharmacist, expectations of the pharmacist, and previous collaborative experiences. A chi-square test was used for statistical analysis. Results: In total, 357 pharmacists and 232 veterinarians participated in the study. Both professions agreed that pharmacist-veterinarian collaboration is important in order to optimize veterinary patient care (chi-square (1, N=589)=7.7, p=0.006). Overall, veterinarians were more likely to identify an important role of the community pharmacist to be compounding medications (chi-square (1, N=589)=26.7, p<0.001) compared to counseling pet owners (chi-square (1, N=589)=171.7, p<0.001). Both groups reported similar levels of agreement regarding the importance for pharmacists to have adequate knowledge of veterinary medicine. Conclusions: Our study found that while both pharmacists and veterinarians conveyed a positive attitude regarding interprofessional collaboration, they disagreed on what role the pharmacist should play in the care of veterinary patients. Rectifying the discordant perceptions of these health care professionals may be critical to developing collaborative initiatives and optimizing veterinary patient care.